PERAN HAKIM MEDIATOR DALAM SENGKETA KEWARISAN DI PENGADILAN AGAMA PINRANG KELAS 1B - Fitriani Saudu Fite; Muh. Jamal Jamil; A. Intan Cahyani (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2022)
In the thesis entitled The Role of Mediator Judges in Mediation of Inheritance Disputes at the Pinrang Religious Court Class 1B discusses the role and ideas of mediators in the settlement of inheritance disputes at the Pinrang Religious Court Class IB and also discusses the problems faced by the mediator judges when mediating inheritance cases. . Which causes a lack of public trust in the judiciary which is considered slow and convoluted in resolving a case, therefore the author wants to know the roles and ideas that are carried out by mediators in resolving inheritance cases in mediation and what are the obstacles for mediators in dealing with mediation. inheritance case in the Pinrang Religious Court Class 1B. The type of research used is field research, using a formal legality approach and a social approach. This data was obtained from judges and mediator judges of the Pinrang Religious Court. Data collection methods used in this study were observation, interviews, documentation and searches of various literatures or references. Data processing and analysis techniques were carried out in three stages, namely: data reduction, data presentation, and drawing conclusions. The results of the study state that the role of the mediator judge in resolving inheritance disputes at the Pinrang Religious Court Class IB has an important role in conducting the mediation process based on the results of interviews with judges as mediators at the Pinrang Religious Court Class I B. It's just that the success achieved by the mediator in resolving disputes inheritance in the Pinrang Religious Court has not been effective due to several inhibiting factors, both from the mediator himself and from the parties concerned. The implication of this research is that there is a mediation process carried out by the mediator in the Court with the aim of increasing the process of resolving cases, especially in mediation. The mediator must play a role in carrying out the best dispute resolution so that the mediation process runs optimally, so that the parties feel satisfied and no party is harmed, this research is expected to have an impact on increasing the success of the mediator in mediating parties who have cases in the Religious Courts.